ANALISIS ASUHAN KEPERAWATAN PADA REMAJA PUTRI DENGAN MASALAH KEPUTIHAN MELALUI INTERVENSI REBUSAN DAUN SIRIH MERAH - Refa Refiana, Rusmawan (2022)
Vaginal discharge is one of the problems faced by young women during adolescence which can be a serious problem that should not be taken lightly. If vaginal discharge has become pathogenic, it can be fatal if not treated properly, leading to problems such as infertility and pelvic inflammation. The use of betel leaf which naturally contains antibiotics and antiseptics is one solution to overcome vaginal discharge. The purpose of this nursing care is to overcome the problem of vaginal discharge in adolescent girls by using the intervention of red betel leaf decoction. The intervention of giving red betel leaf decoction was carried out for seven consecutive days and was used as cebokan water. The results of the implementation showed that after being given boiled water of red betel leaf for 7 consecutive days, there was a decrease in the incidence of vaginal discharge from abnormal to normal in both the main managed clients and resume clients. These results indicate that the use of red betel leaf boiled water has an effect on overcoming vaginal discharge in adolescents. Young women are advised to use red betel leaf decoction to treat vaginal discharge. Keywords: red betel leaf, vaginal discharge, young women